Drug use for grown-ups : chasing liberty in the land of fear - Hart, Carl L. (Penguin Press, 2021)
"From one of the world's foremost experts on the effects of recreational drugs on the mind and body, a powerful argument that the greatest dangers from drugs flow from their being illegal, and a field guide to their use as part of a responsible and happy life. Dr. Carl Hart, Ziff Professor at Columbia University and former Chair of the Department of Psychology, is one of the world's preeminent experts on the effects of so-called recreational drugs on the human mind and body. Dr. Hart also is open about the fact that he uses drugs himself, in a happy balance with the rest of his full and productive life as a colleague, husband, father and friend. In Drug Use for Grown-Ups, he draws on both decades of research and his own personal experience to argue definitively that the criminalization and demonization of drug use is itself far and away the greatest scourge drugs inflict on America. Carl Hart did not always have this view, to put it mildly. He came of age in one of Miami's most troubled neighborhoods at a time when many ills were being laid at the door of crack cocaine. His initial work as a researcher was aimed at proving that drug use caused predominantly bad outcomes. But one problem kept cropping up: the evidence from his research did not support his hypothesis. And indeed, no one else's evidence did either. From the inside of the massively well-funded research side of the American war on drugs, he saw how the inconvenient truth that the facts didn't support the ideology was dismissed, denied and distorted in order to keep fear and outrage stoked, the funds rolling in, and black and brown bodies behind bars. Drug Use for Grown-Ups will be controversial, to be sure: it challenges head-on some of our strongest moral reflexes about drugs and citizenship. The propaganda war, Hart argues, has been tremendously effective. Imagine if the only subject of any conversation about driving automobiles was fatal car crashes. We regulate driving, just as we regulate alcohol. During Prohibition, fatalities from alcohol use skyrocketed, because people didn't know what they were drinking, and hundreds of thousands were inadvertently poisoned. So it is with the opioid epidemic, response has been driven by a mass panic that in many respects reminds Hart of the crack cocaine panic of the 1980's. Drug Use for Grown-Ups offers a radically different vision: of how, when used responsibly, drugs can powerfully enrich and enhance our lives. The nexus of special interests that benefit from drug criminalization and demonization, Hart shows us, has kept this country in a terrible place, but change is beginning to come. Ultimately this is about education: the facts are clear. In every country with a more permissive and humane drug regime, all human outcomes are better, from mortality to addiction to overall quality of life, and the countries with the most permissive regimes, like Portugal and Switzerland, have the best outcomes. We have a long way to go, but the vital conversation this book will generate is an extraordinarily important step."--